Effects of multiple modes of UltraPulse fractional CO2 laser treatment on extensive scarring: a retrospective study - Ge, Xiaojing; Sun, Yute; Lin, Jing; Zhou, Fang; Yao, Gang; Su, Xin (Lasers in medical science, 2022)
The main therapeutic options for extensive scarring (e.g., > 20% of the total body surface area, or TBSA) after burns and trauma have focused on conservative treatments, such as compression, moisturization, and topical agent application. However, these treatments may not achieve optimal effects due to the large size and complexity of the scars. UltraPulse fractional CO 2 laser treatment is a novel approach that is currently a subject of intense interest; this treatment is most widely used to improve texture, pliability, and pigmentation in all types of scars. However, no studies on the independent use of UltraPulse fractional CO 2 laser treatment for extensive scars have been reported. This retrospective study evaluated a total of 21 patients, whose scars covered 20 to 65% TBSA. Scar thickness was measured by ultrasonography before treatment. Personalized treatment modalities and parameters were set according to the scar type and thickness. Scar formation and treatment effects were evaluated by photography, the Patient and Observer Scar Assessment Scale (POSAS), and patients’ judgment of effectiveness. Where the scars covered joints, joint function was assessed by measuring the maximum range of motion (ROM). With laser therapy, scars became flatter and lighter; furthermore, pruritus, pain, and discomfort decreased significantly. POSAS scores significantly decreased after laser therapy, including the item scores for pain and pruritus. There were no instances of joint contracture, ROM reduction, apparent functional impairment, serious adverse events, or comorbidities. This study demonstrates the safety and efficiency of UltraPulse fractional CO 2 laser treatment for extensive scarring.